Gut Microbiota On Erectile Dysfunction : a Systematic Review - Dwiprawira, Revantoro Artha; Bintoro, Ariyo Sakso (Jurnal sosial dan sains, 2025)
Erectile dysfunction (ED) has significant physical and psychological effects on both patients and their partners. Beyond disrupting sexual relationships and family dynamics, ED is often associated with comorbidities such as anxiety, depression, and other mental health disorders. A potential relationship is suggested by variations in our gut microbiota the composition between ED patients and healthy people. This study aims to evaluated relationship between gut microbiota and ED. Materials & Methods : A systematic review was conducted with PRISMA 2020 guidelines, with PICO framework to focus on individuals with ED. The intervention analyzed was gut microbiota compared to healthy controls, with the primary outcome being gut microbiota associated with ED. Search was performed across PubMed, Scopus, Web of Science, and Cochrane Library from 2020 to 2025 using keywords such as "gut microbiome," "gut microbiota," "intestinal microbiome," and "gut flora" combined with "erectile dysfunction." Inclusion and exclusion criteria were applied, and the risk of bias in studies was assessed using the Newcastle-Ottawa Quality Assessment Scale. Results : A total of 64 studies underwent screening, 7 were included in the final analysis. The results showed correlation between ED and changes in the gut microbiota. A higher risk of ED was associated with increased populations of Lachnospiraceae, Oscillibacter, Tyzzerella3, Senegalimassilia, and Actinomyces. On the other present, a lower risk of ED was related to Ruminococcaceae UCG013, Coprococcus 1, Lachnospiraceae FCS020, Prevotella, and Bifidobacterium. Moreover, ED patients had more species of Streptococcus, Subdoligranulum, Bacteroides, Fusobacterium, and Escherichia-Shigella genera compared to species Blautia, Roseburia, Ruminiclostridium 5, and Lactococcus. Conclusion : The role of gut microbiota in ED, with Lachnospiraceae, Oscillibacter, Tyzzerella3, and Senegalimassilia increasing risk, while Ruminococcaceae UCG013 is protective. However, further research is needed to understand microbial mechanisms and explore gut microbiota modulation as a potential therapeutic strategy.